2002
DOI: 10.1109/49.983348
|View full text |Cite
|
Sign up to set email alerts
|

On bandwidth-efficient multiuser-space-time signal design and detection

Abstract: Signals designed for transmission over multiple transmit antennas are capable for achieving significant capacity gain. Traditional approaches aim at improving the single-user link with a centralized control over the set of transmit antennas. In this paper, by considering a set of independent and synchronized users communicating with the base station on the up-link, the joint signal can be viewed as space-time coded signal without a centralized control. Co-channel/inter-antenna interference presents a major imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The problem of optimum grouping for a method based on ZF and hard cancellation was considered in [15]. An alternative in [10] is to assign users arbitrarily to groups, then to order the groups.…”
Section: E Detection Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…The problem of optimum grouping for a method based on ZF and hard cancellation was considered in [15]. An alternative in [10] is to assign users arbitrarily to groups, then to order the groups.…”
Section: E Detection Ordermentioning
confidence: 99%
“…In a series of simulations, we compared the performances of IMUD, the group ML with MMSE suppression of [10] (denoted GD in the results), simple MMSE and MMSE V-BLAST [18]. Throughout this section, the notation ( ) …”
Section: Performance Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The established user-wise ordering property offers a potential advantage of computation reduction based on group-wise data processing; an associated low-complexity algorithm implementation which further exploits the OSTBC structure is derived in [7]. Recently it is reported that the uplink performance of MU-OSTBC systems can be further improved by incorporating the codeword rotation technique [14]. Our discussions below, however, will not take such a codeword mapping into account to better focus on the intrinsic properties introduced by OSTBC.…”
mentioning
confidence: 99%
“…Our discussions below, however, will not take such a codeword mapping into account to better focus on the intrinsic properties introduced by OSTBC. It is noted that group-wise detectors are also proposed in [14] for multiuser signal separation. The MMSE based solution in [14, p-325] is basically a parallel interference suppression scheme but does not exploit the algebraic property of OSTBC; the associated refined version with signal ordering in [14, p-326] is however virtually similar to the one-step PIC method introduced in [13].…”
mentioning
confidence: 99%